PROBLEMS OF THE 2013 CURRICULUM:A CASE STUDY OF IMPLEMENTING ENGLISH ASSESSMENT IN THE 2013 CURRICULUM - Husnayain, Arini (Universitas Islam Lamongan, 2016)
The objectives of this study are to explain the implementation of assessment process in teaching English based on curriculum 2013 and to identify the problems faced by English teachers of MAN Lamongan when teaching English based on curriculum 2013.Keywords: implementation, curriculum 2013, assessment